2016
DOI: 10.4012/dmj.2016-005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and angiogenic potential of xenogeneic bone grafting materials: Role of periodontal ligament cells

Abstract: Adequate revascularization is a prerequisite for successful healing of periodontal bone defects. This study characterized three different xenogeneic bone grafting materials: Gen-Os of equine and porcine origins, and anorganic Bio-Oss. We also investigated their angiogenic potential. All materials were composed of poorly crystalline calcium oxide phosphate, with Bio-Oss exhibiting a carbonated phase and larger particle size and both Gen-Os showing the presence of collagen. Both Gen-Os materials significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…This is in agreement with an in vitro study that showed high rates of endothelial cell proliferation and capillary‐like structures formation in cultures with Gen‐Os (Rombouts et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with an in vitro study that showed high rates of endothelial cell proliferation and capillary‐like structures formation in cultures with Gen‐Os (Rombouts et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Spectra of both Bio‐Oss ® and Gen‐Os ® show, in addition, a low intensity double‐band at 1410‐1460 cm −1 that corresponds to stretching vibration of CO 3. However, Bio‐Oss ® have an higher intensity compared to Gen‐Os ® , indicating an higher amount of carbonate compounds …”
Section: Resultsmentioning
confidence: 97%
“…It reaches an Isoelectric Point (IEP, the point where the ζ‐potential is equal to zero, and where the surface charge is balanced) at pH of 5.74. A possible explanation of this behavior is that the composition of Bio‐Oss ® , analyzed through IR, reveals the presence of hydroxyapatite and calcium carbonate, and a lower amount, compared to Gen‐Os ® of β‐TCP . This is probably the reason for the different magnitude of the ζ‐potential between the two xenograft materials analyzed and among Bio‐Oss ® and the other wholly inorganic bone fillers tested.…”
Section: Discussionmentioning
confidence: 97%
“…Grooves were made on stent to ensure precise repeated probing measurements. (9) Clinical parameters were measured prior to surgery: baseline, 6 and 12 month after surgery. Plaque index (PI) (10) and gingival index (GI) (11) were recorded, in addition measurements of PD, and attachment level (AL) (12) , the PD and AL were measured by using a Marquis periodontal probe and recorded to the neatest millimeter, the measurements were repeated at the same grove which designed to the periodontal defect.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…On the other hand, significant increase in endothelial cell proliferation was observed in cultures with both Gen-Os conditioned media, but not with that of Bio-Oss. (9) According to our knowlodge there is no studies are presently available for the treatment of periodontal intrabony defects by Cortico-cancellous xenograft [Osteobiol Gen-Os].…”
Section: Introductionmentioning
confidence: 99%